The Use of the Arts of Adaptation and Allusion in Arabic Poetry from West Africa and It Is Reading In the Context of Religious Intertextuality - Maiga, Mohamadou Aboubacar (Fırat University, 2022)
It is known that the text of the Qur'an is artistic prose that has reached an unprecedented level in terms of its unique style, superiority, and robustness. Likewise, it can be said for hadith texts reach the peak of eloquence and beauty. Scholars have paid attention to the Qur'an and Hadith texts for centuries in their scientific studies. There are also poets among those who care. Inspired by both texts, they tried to use their style in their odes and literary products through quotation, reference, compensation, and similar arts. From this point of view, our research aims to examine the phenomenon of religious intertextuality in African Arabic poetry -on the condition that the study is limited to the West African region- and to explain its places. In addition to learning to what extent the African poet was influenced by the style, language structure, and methods of the Qur'an and hadith texts, it also explores the relationship adopted between his literary references. What gives this study important is that it attempts to apply one of the modern critical theories (intertextuality) to Arabic poetry from West Africa, which many researchers do not know about. This research will prove the rooting of the art of Arabic poetry in West Africa through its intertextuality with the ancient Arab heritage, as well as the validity of its use as a scientific material for contemporary theories. During the research, it was determined that various religious intertextuality was used in the poems of African poets. The poets did not adhere to a certain form in their poems, on the contrary, they used different methods at every stage of their poems. This revealed their culture and knowledge of Arabic literature and poets and showed the extent of their devotion to the Qur'an and Sunnah. Likewise, by referring to historical events and religious people with a religious dimension, they revealed creativity in their poems. For this reason, they were able to paint the most beautiful artistic paintings, which impressed both the reader and the listener.

Kur'ân-ı Kerîm, metninin eşsiz üslubu, üstünlüğü ve sağlamlığı bakımından emsalsiz bir mertebeye ulaşmış sanatsal bir nesir olduğu bilinmektedir. Bu tarif aynı şekilde belagatin ve güzelliğin doruğuna ulaşan hadis metinleri için de yapılabilir. Âlimler asırlar boyunca çeşitli eser ve araştırmalarında Kur'ân ve Hadis metinlerine yer vermeye itina göstermişlerdir. Buna İtina gösterenler arasında şâirler de vardır. Onlar her iki metinden de esinlenerek kasidelerinde ve edebi ürünlerinde iktibas, telmih, tazmin vb. sanatlar yoluyla kendi üsluplarını kullanmaya çalışmışlardır. Bundan hareketle, araştırmamız Afrika Arap şiirinde dinî metinlerarasılık olgusunu -çalışmanın Batı Afrika bölgesi ile sınırlı olması koşuluyla- incelemeyi ve yerlerini açıklamayı amaçlamaktadır. Afrikalı şâirlerin Kur’ân ve hadis metinlerinin üslubu, dil yapısı ve yöntemlerinden ne ölçüde etkilendiğini öğrenmenin yanı sıra, edebi referansları arasında benimsenen ilişkiyi araştırmak hedeflenmiştir. Bu çalışmayı önemli kılan şey, modern eleştirel teorilerden (metinlerarasılık) birçok araştırmacının bilmediği Batı Afrika Arap şiirine uygulanmaya çalışmasıdır. Bu araştırma, Arap şiir sanatının Batı Afrika'daki köklerini, eski Arap mirasıyla metinlerarasılık yoluyla ve çağdaş teoriler için bilimsel bir materyal olarak kullanımının geçerliliğini kanıtlayacaktır. Araştırma sırasında Afrikalı şâirlerin şiirlerinde çeşitli dinî metinlerarasılık kullanıldığı tespit edilmiştir. Şâirler şiirlerinde belirli bir şekle bağlı kalmamış, aksine şiirlerinin her safhasında farklı yöntemler kullanmışlardır. Bu, onların Arap edebiyatı ve şâirleriyle ilgili kültürlerini ve bilgilerini ortaya koymuş ve onların Kur’ân ve Sünnete bağlılıklarının boyutunu göstermiştir. Aynı şekilde tarihsel olaylara ve dini boyutu olan dini kişilere çokça atıfta bulunarak, şiirlerinde yaratıcılık ortaya koymuşlardır. Bu nedenle de onlar, hem okuyucu hem de dinleyicinin etkilendiği en güzel sanatsal tabloları resmedebilmişlerdir.
Batı Afrika Arap Şiirlerinde Kullanılan İktibâs ve Telmih Sanatlarını Dinî Metinlerarasılık Bağlamında Okumak
Keywords: Religious Studies; Din Araştırmaları